Comparison of abstraction scenarios simulated by SWAT and SWAT-MODFLOW. Issue 4 (12th March 2019) - Molina-Navarro, Eugenio; Bailey, Ryan T.; Andersen, Hans Estrup; Thodsen, Hans; Nielsen, Anders; Park, Seonggyu; Jensen, Jacob Skødt; Jensen, Jacob Birk; Trolle, Dennis
ABSTRACT: In hydrological modelling of catchments, wherein streams are groundwater-fed, an accurate representation of groundwater processes and their interaction with surface water is crucial. With this purpose, a coupled model was recently developed linking SWAT (Soil and Water Assessment Tool) with the fully-distributed groundwater model MODFLOW (Modular Groundwater Flow). In this study, SWAT and SWAT-MODFLOW were applied to a Danish groundwater-dominant catchment, simulating groundwater abstraction scenarios and assessing the benefits and drawbacks of SWAT-MODFLOW. Both models demonstrated good performance. However, SWAT-MODFLOW provided more realistic outputs when simulating abstraction: the decrease in streamflow was similar to the volume of water abstracted, while in SWAT the impact was negligible. SWAT also showed impacts on streamflow only when abstractions were taken from the shallow aquifer, not from the deep aquifer. Overall, SWAT-MODFLOW demonstrated wider possibilities for groundwater analysis, providing more insights than SWAT in supporting decision making in relation to environmental assessment.